2020
DOI: 10.1103/physrevb.102.075126
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field induced structural changes in magnetite observed by resonant x-ray diffraction and Mössbauer spectroscopy

Abstract: When a magnetic field is applied to a single crystal of magnetite at 124 K > T > 50 K, the monoclinic c M axis, which is the easy magnetization axis, switches to one of the 100 cubic directions, nearest to the direction of the magnetic field, and the phenomenon known as an axis switching (AS) occurs. A global symmetry probe, resonant x-ray scattering, and a local probe, Mössbauer spectroscopy, are used to better understand the mechanism of axis switching. The behavior of three subsystems ordered below the Verw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The obtained results can be compared with other studies which probe the local charge distribution on Fe B ions. The NMR and Mössbauer measurements combined with DFT calculations revealed that all B-sites can be divided into three groups with the ratio 8:5:3 [18,19,77,78]. The first group consists of 8 Fe 3+ ions, the second group includes 5 Fe 2+ ions in which electrons occupy the d xz or d yz orbitals, and the third group comprises 3 Fe 2+ ions with occupied d xy orbitals.…”
Section: Final Discussion and Summarymentioning
confidence: 99%
“…The obtained results can be compared with other studies which probe the local charge distribution on Fe B ions. The NMR and Mössbauer measurements combined with DFT calculations revealed that all B-sites can be divided into three groups with the ratio 8:5:3 [18,19,77,78]. The first group consists of 8 Fe 3+ ions, the second group includes 5 Fe 2+ ions in which electrons occupy the d xz or d yz orbitals, and the third group comprises 3 Fe 2+ ions with occupied d xy orbitals.…”
Section: Final Discussion and Summarymentioning
confidence: 99%
“…24 , 25 Further Mössbauer and resonant X-ray experiments have suggested that trimeron direction changes around a fixed central Fe 2+ ion when the easy magnetization axis of the Cc phase is switching by an applied magnetic field. 27 Recent phonon calculations for the Cc structure have shown good agreement with inelastic neutron, X-ray, and nuclear scattering data, revealing strong trimeron–phonon coupling, especially for trimerons oriented parallel to the axes of the monoclinic Cc cell. 28 …”
Section: Resultsmentioning
confidence: 78%
“…The four signals are in an 8:8:5:3 ratio to account respectively for 8 A-site Fe 3+ ions, 8 B-site Fe 3+ ions, 5 B-site Fe 2+ ions where the extra electron occupies d xz or d yz orbitals, and 3 B-site Fe 2+ ions with the extra electron in the d xy orbital. The latter group is distinct as the d xy orbitals lie perpendicular to the magnetization in the Cc structure giving rise to lower effective magnetic fields and larger electric field gradients, and they also have distinctive NMR frequencies. , Further Mössbauer and resonant X-ray experiments have suggested that trimeron direction changes around a fixed central Fe 2+ ion when the easy magnetization axis of the Cc phase is switching by an applied magnetic field . Recent phonon calculations for the Cc structure have shown good agreement with inelastic neutron, X-ray, and nuclear scattering data, revealing strong trimeron–phonon coupling, especially for trimerons oriented parallel to the axes of the monoclinic Cc cell …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations